Comparable Effects ofIsolated and CombinedAssisted and Resisted Sprint Training Programmes on Cardio Vascular Fitness among College Women Athletes - THENMOZHI, S.; PARTHIBAN, Dr. I. JOHN (South Eastern European Journal of Public Health, 2025)
The present study was designed to find out the effects of isolated and combinedassisted and resisted sprint training programmeson cardio vascular fitness among collegewomen athletes. For this purpose,sixty(N=60) college female athletes who were studying various colleges affiliated to Bharathidasan University, Tiruchirappalli,Tamilnadu India were selected randomly as subjects. The age of the subjects was ranged between 18-21 years. The subjects were assigned at random into four groups of fifteen each (n=15) namely, Assisted Sprint Training Group (ASTG), Resisted Sprint Training Group (RSTG), Combined Assisted and Resisted Sprint Training Group (ARSTG), and Control Group (CG).Group-I underwent Assisted Sprint Training, Group-II underwent Resisted Sprint Training, Group-III underwent Combined Assisted and Resisted Sprint Trainingand Group-IV acted as Control. For all three experimental groups, the training period was limited to twelve weeks, and there could be no more than three sessions each week. The training schedule for mixed assisted and resisted sprint training was limited to alternate weeks for a total of twelve weeks. Cooper's 12-minute run/walk test were used to measure the dependent variable of cardiovascular fitness. Every subject was tested for every one of the chosen factors both before and right after training. The pre and post assessment developments in the groups were analyze with t-test and analysis of covariance. The Scheffe’s post hoc test was also calculated for pair wise comparisons. For all cases 0.05 level of confidence was fixed. The study's findings demonstrated that there was a significant difference in cardiovascular fitness between all three experimental group such as Assisted Sprint Training Group (ASTG), Resisted Sprint Training Group (RSTG), and Combined Assisted and Resisted Sprint Training Group (ARSTG). Additionally, the study's findings supported that the Combined Assisted and Resisted Sprint Training Group (ARSTG) outperformed the Assisted Sprint Training Group (ASTG) and Resisted Sprint Training Group (RSTG) in terms of cardiovascular fitness.